Design and implementation of monitoring and warning (IOT) system for electricity poles - AL-Hammoudi, Jumana Amer; Jasim, Basil H. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
There are many serious accidents on human life caused by electric current columns, and it is possible for the Internet of Things to find solutions to prevent the risks that occur, as in many fields such as medicine, agriculture, industry and others. In this paper, we will show monitoring and tracking of the current that passes through the electrical poles and the possible leakage, in addition to monitoring the temperature and humidity in the area, and knowing the condition of the light in the column according to morning and evening, this proposed system that will perform a general purpose added to the region. using Open source NODE MCU board, GPS positioning, current sensor, temperature and humidity sensor that provide desired data via open source platforms that we have chosen to be ThingSpeak that easily to handle.